Pemberdayaan Generasi X dalam Meningkatkan Ekonomi Keluarga melalui UMKM Kacang Sembunyi Berbasis ABCD di Desa Klantingsari - Ahmad Aly Syukron Aziz Al Mubarok; Devi Irma Purwati; Janitra Adela Issanti Ramadhani; Gista Naruliya Siswanti; Himatul Allya; Juwariyah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
Generation X (1965-1980) had an important role in the economy of rural families, but many faced obstacles in managing their businesses due to limited managerial and marketing skills. Their empowerment through the development of MSMEs is a solution to improve skills and innovation. One effective approach is Asset-Based Community Development (ABCD), which harnesses local potential to empower communities. This study examines the application of ABCD in the hidden peanut MSMEs business in Klantingsari Village managed by Miftakhul Karimah since 2013. This approach has proven successful in maximizing local potential, developing managerial and marketing skills, and increasing the capacity of generation X to manage their businesses. Through this research, it is hoped that it can provide a deeper understanding of local asset-based empowerment to improve the economic welfare of rural communities, especially generation X, and create jobs.